1982
DOI: 10.1136/bmj.285.6343.691-a
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol: side effects in a newborn infant.

Abstract: SHORT REPORTSReversible male subfertility due to hyperthyroidism Hyperthyroidism in women may cause oligomenorrhoea, amenorrhoea, and failure of ovulation. In men gonadal dysfunction is less apparent, though loss of libido, reduced potency,' and gynaecomastia2 may occur. We describe a man who presented with subfertility due to thyrotoxicosis and in whom normal fertility was restored with antithyroid drug treatment. Case reportA 26-year-old man with a one-year history of attempted conception was referred to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Table 6 shows the quality of the nine case series [ 26 , 27 , 48 , 56 , 57 , 61 , 62 , 64 , 65 ]. Table 7 shows the quality of the 15 case reports [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 6 shows the quality of the nine case series [ 26 , 27 , 48 , 56 , 57 , 61 , 62 , 64 , 65 ]. Table 7 shows the quality of the 15 case reports [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one of the fifty-five included articles examined whether bradycardia was found in neonates exposed to beta-blockers either in utero or during lactation [ 27 , 28 , 30 , 32 , 33 , 34 , 35 , 37 , 38 , 40 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Table 8 presents 28 of the articles [ 27 , 28 , 30 , 32 , 33 , 34 , 35 , 37 , 38 , 40 , 43 , 44 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cardioselective P-adrenergic blocking agents have been used with some success in the control of hypertension during pregnancy although side effects in the newborn infants have been reported (Dumez et al 1981: Woods & Morrell 1982. Lagercrantz & Bistoletti (1977) showed that the concentrations of catecholamines in the cord blood at birth are elevated, especially after a complicated delivery.…”
mentioning
confidence: 99%